Biological interactions of ferromagnetic iron oxide–carbon nanohybrids with alveolar epithelial cells. (23rd May 2022) - Vercellino, Silvia; Kokalari, Ida; Liz Cantoral, Mayra; Petseva, Vanya; Cursi, Lorenzo; Casoli, Francesca; Castagnola, Valentina; Boselli, Luca; Fenoglio, Ivana
Abstract : Iron oxide nanoparticles with a carbon shell (IONP@C) showed good colloidal stability in the biological environment, no cytotoxic effects and a peculiar intracellular trafficking pathway on a widely employed model of alveolar epithelial cells. Abstract : Iron oxide nanoparticles (IONPs) have been largely investigated in a plethora of biological fields for their interesting physical–chemical properties, which make them suitable for application in cancer therapy, neuroscience, and imaging. Several encouraging results have been reported in these contexts. However, the possible toxic effects of some IONP formulations can limit their applicability. In this work, IONPs were synthesized with a carbon shell (IONP@C), providing enhanced stability both as colloidal dispersion and in the biological environment. We conducted a careful multiparametric evaluation of IONP@C biological interactions in vitro, providing them with an in vivo -like biological identity. Our hybrid nanoformulation showed no cytotoxic effects on a widely employed model of alveolar epithelial cells for a variety of concentrations and exposure times. The IONP@C were efficiently internalized and TEM analysis allowed the protective role of the carbon shell against intracellular degradation to be assessed. Intracellular redistribution of the IONP@C from the lysosomes to the lamellar bodies was also observed after 72 hours.